Navigating reproductive rights: an exploration of human dignity and healthcare costs in the abortion debate - Dzelme, Katrīna (Riga Graduate School of Law, 2024)
The abortion debate reflects the complex interplay of human dignity, reproductive rights, legal frameworks, and healthcare access. The issue lacks a singularly correct solution due to the diversity of perspectives available. Upholding reproductive rights as fundamental human rights is essential for ensuring healthcare access and preserving human dignity and autonomy. Courts have struggled to recognize the mother's autonomy with the foetus’s right to life but recognize women's reproductive rights. Laws restricting abortion are increasingly viewed as unconstitutional due to outdated justifications. Access to safe and affordable abortion care is crucial for upholding reproductive rights and human dignity, however, the financial barriers to safe abortion care disproportionately affect women and potentially violate their dignity and right to private life. Notably, access to safe abortion has significant implications for healthcare expenditures.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Human rights law; Abortion; reproductive rights